Surgical treatment of the ischemic heart disease with lowered contractility of left ventricle and mitral valve insufficiency - S. A. Rudenko; A. V. Rudenko; Yu. V. Kaschenko; V. P. Zakharova (Клінічна хірургія, 2020)
Objective. To determine the impact of the mitral valve insufficiency in patients, suffering ischemic heart disease with lowered contractility of left ventricle and methods of its treatment.